MACROECONOMIC TRENDS IN EMPLOYMENT IN UZBEKISTAN - Shayusupova Nargiza Turgunovna; Amirdjanova Sitora Sunnat qizi (Labor economics and human capital, 2023)
This article is devoted to the issues of increasing employment in Uzbekistan in the context of modern economic development of the republic. The article systematizes the theoretical and methodological approaches to the category of "employment" and discusses its relationship with macroeconomic growth and demographic factors. In addition, a retrospective analysis of the development of the labor market and employment has been conducted in this article. In accordance with the development strategy of new Uzbekistan for 2022-2026, the main directions of further development of employment have been identified by giving priority to youth policy.